(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Background This Covid-19 disease is declared as a pandemic situation all over the world and it gives a challenge to all sector especially to education sector. Due to all restriction made up by the government for control and prevention of the disease this make a huge change in the learning method of the educational sector. These changes for the undefined period of time.Methods In this paper we want to identify that scope of online educational trainings and classes through that can deliver the knowledge and how it can be beneficial for the students, teachers, institutions and all knowledge-based industries. Descriptive study this theoretical integration shows that how this pandemic situation changes the teaching-learning methodology.Conclusion This Paper Concludes teaching and learning is not discontinuing in this situation still there are many ways e.g. Online teaching, Webinars, E-Quiz, E-Library or free Courses of renowned institutions through that learning is unstoppable. These innovative solutions utilizing technology bridge the gap between learner and educator in these unparalleled circumstances.